Análise da competitividade da acerola no estado de São Paulo - Lourenzani, Wagner Luiz [UNESP]; Lourenzani, Ana Elisa Bressan Smith [UNESP]; Pigatto, Gessuir [UNESP]; Pigatto, Giuliana Aparecida Santini [UNESP]; Queiroz, Timóteo Ramoz [UNESP] (My University, 2015)
This research aims at analyzing competitiveness of acerola production in São Paulo, Brazil. Junqueirópolis region is the largest acerola producer in the state and third in the country. The region is characterized by a clear territorial delimitation, an important position in the socio-economic scenario of the regional horticulture, presents an agglomeration of economical agents and there are partnership initiatives and cooperation and is an activity representative of small and medium producers. The methodology adopted was used for analysis of competitiveness of agro-industrial chains proposed by Silva and Batalha (1999). The results indicate that cooperation, among other factors, has promoted benefits that contribute to the competitiveness of the activity. Finally, the results can be used as an instrument for fostering the development of public and private policies, aiming at regional development.
Competitiveness analyses of acerola in Sao Paulo State, Brazil
Keywords: Acerola; Competitiveness; Cooperation; Networks